Self-awareness deficits associated with lower treatment motivation in cocaine addiction. (2nd January 2019) - Castine, Benjamin R.; Albein-Urios, Natalia; Lozano-Rojas, Oscar; Martinez-Gonzalez, Jose M.; Hohwy, Jakob; Verdejo-Garcia, Antonio
ABSTRACT: Background : Individuals with cocaine use disorder (CUD) often display behaviours that are paradoxically misaligned with their situation. Typical examples include poor treatment motivation and inconsistent self-reported craving. These behaviours may reflect impairments in the awareness of one's own behaviour. Objectives : We examined whether impaired self-awareness of addiction-related frontostriatal dysfunction (i.e., symptoms of apathy, disinhibition, and executive dysfunction) was associated with treatment motivation and craving. Methods : Sixty-five outpatients with CUD (57 male) and their informants (those who knew the patient well) completed parallel self and informant versions of the Frontal Systems Behaviour Scale. Self-awareness was indexed through the discrepancy between self and informant scores in the three sub-scales; apathy, disinhibition and executive dysfunction. The University Rhode Island Change Assessment Scale assessed treatment motivation. Self-reported craving was assessed using a visual analogue scale. Multiple linear regression models examined associations between self-awareness and treatment motivation and craving, adjusting for sociodemographic factors and lifetime drug use. Results : We found an inverse relationship between self-awareness of symptoms of disinhibition and treatment motivation maintenance. Although impaired awareness of disinhibition was also correlated with craving, this association was not significant after adjusting for sociodemographic factors and drug use. The apathy and executive dysfunction awareness scores were not associated with treatment motivation or craving. Conclusion : We show that people with lower insight into their disinhibition problems (e.g., impulsivity, mood instability) have more problems maintaining motivation when initiating treatment. Findings suggest that self-awareness interventions could be useful to prevent premature treatment dropout and improve addiction treatment outcomes.